Adaptive Management as an Effective Strategy: Interdisciplinary Perceptions for Natural Resources Management. - Dreiss, Lindsay; Hessenauer, Jan-Michael; Nathan, Lucas; O'Connor, Kelly; Liberati, Marjorie; Kloster, Danielle; Barclay, Janet; Vokoun, Jason; Morzillo, Anita (Environmental Management, 2017)
Adaptive management is a well-established approach to managing natural resources, but there is little evidence demonstrating effectiveness of adaptive management over traditional management techniques. Peer-reviewed literature attempts to draw conclusions about adaptive management effectiveness using social perceptions, but those studies are largely restricted to employees of US federal organizations. To gain a more comprehensive insight into perceived adaptive management effectiveness, this study aimed to broaden the suite of disciplines, professional affiliations, and geographic backgrounds represented by both practitioners and scholars. A questionnaire contained a series of questions concerning factors that lead to or inhibit effective management, followed by another set of questions focused on adaptive management. Using a continuum representing strategies of both adaptive management and traditional management, respondents selected those strategies that they perceived as being effective. Overall, characteristics (i.e., strategies, stakeholders, and barriers) identified by respondents as contributing to effective management closely aligned with adaptive management. Responses were correlated to the type of adaptive management experience rather than an individual's discipline, occupational, or regional affiliation. In particular, perceptions of characteristics contributing to adaptive management effectiveness varied between respondents who identified as adaptive management scholars (i.e., no implementation experience) and adaptive management practitioners. Together, these results supported two concepts that make adaptive management effective: practitioners emphasized adaptive management's value as a long-term approach and scholars noted the importance of stakeholder involvement. Even so, more communication between practitioners and scholars regarding adaptive management effectiveness could promote interdisciplinary learning and problem solving for improved resources management.